Equity in Health Care: A Qualitative Study with Refugees, Health Care Professionals, and Administrators in One Region in Germany. (25th February 2020) - Hahn, Karolin; Steinhäuser, Jost; Goetz, Katja
Abstract : Introduction . Equity in health is an essential issue and it would appear that it is not guaranteed for all human beings, especially refugee groups. The aim of this qualitative descriptive study was to explore the experiences of refugees, health care professionals, and administrators of refugee health care in a host country. Methods . The study used qualitative methods which consisted of a convenience sample of stakeholders directly and indirectly involved in care for refugees and refugees themselves. The study participants were located in a rural area in the federal state of Schleswig-Holstein, Germany. Focus groups and interviews were conducted with 25 participants. A semistructured interview guideline was used for the focus groups and interviews. The data were evaluated using qualitative content analysis. Results . Four main categories were identified which are important for equity in health care: legal aspects, sociocultural aspects, environmental aspects, and communication aspects. Legal frameworks and language barriers were perceived as strong barriers for accessing health care. Conclusions . The findings suggest that the host countries should address the specific needs of this population group at a systemic and individual level. Based on the views of the participants interviewed it can be concluded that the refugee population group is particularly affected by limited access to health care services. Bureaucratic barriers, unfamiliarity with a new health system, and language issues all contribute to limiting access to health care services.